SELF-EFFICACY (Perspektif Teori Kognitif Sosial dan Implikasinya terhadap Pendidikan) - Mukhid, Abd. (State Islamic Institute of Madura, 2009)
Self-efficacy is judgement of a person to his acabilities to plan and implement the action to reach certain goals. Social cognitive theory views self-efficacy as one’s beliefs to his own capasity in completing the assigned duties. This theory lies on three factors of reciprocal determinism, personal factors, behaviors, and environmental influence, which has positive impacts to be implemented in education.